The Utilization of Learning Technology to Improve Learning Outcomes in Islamic Education for Students in the Digital Age - Ainunisa, Ulfa; Syafi'i, Imam; Jatmiko, Agus (Al-Fikru: Jurnal Ilmiah, 2025)
The planned and systematic use of information and communication technology devices, media, and resources is essential to support effective learning in the era of globalization. The challenges of teaching Islamic Education at Yasmida Ambarawa Senior High School have prompted the need for technology-based innovation. This study aims to analyze the use of learning technology, particularly the interactive digital media Kahoot, in improving Islamic education learning outcomes. The research method employed a qualitative approach through observation, interviews with teachers and the school principal, and documentation of student learning outcomes. The results indicate that the integration of Kahoot in learning creates a more engaging, interactive, and motivating learning environment, encouraging students to participate actively. Improvements were observed in the cognitive, affective, and psychomotor aspects of the students. Additionally, Kahoot's real-time feedback feature accelerates evaluation and improvement of students' understanding. The implications of this study emphasize the importance of enhancing teachers' competencies in educational technology, developing diverse digital media, and providing technological facilities in schools. The integration of educational technology has proven to be an effective strategy for improving the quality and outcomes of Islamic education in the present era.